Avaliação do tomateiro em função das alterações nas propriedades químicas promovidas pela incorporação de CaCC>3, composto e/ou resíduos de aguapé (Eichhomia crassipes (Mart) Solms), em um neossolo flúvico - Alvarez Lazo, Ronald (2005)
In Igarapé do Meio town the subsistence agriculture occurs in small areas with cultures of maize, rice, beans, cassava and others. Low natural fertility of the land and the lack of technologies adjusted for the agricultural exploration cause low crop productivity. The waters when recoil from rivers and lakes allows to crop the low land rice with high leveis of productivity in function of lands fertilization because of rivers flood. Low price of the rice in the local market has instigated the small farmers the search for altemative cultures that present a bigger value of market, to use the advantage of a high natural fertility of flood plain. The viability of the plantation in cultures with bigger value of market as the vegetables depends on the correction of deleterious efifect of the soil acidity that can inhibit the growth of cultures as the tomato plant. This work, aimed the use of water-hyacinth’s (Eicchomia crassipes (Mart.) Solms) biomass that is accumulated in the flooded fields of town, for use in a compost way or as incorporated to soil waste way for fertilization, in such a way can substitute the calcareous rock in the correction of the raised soil acidity. Four trials in statistical delineation entirely randomized with 4 repetitions (Trials I,II, III) and 4 repetitions (Trial IV) had been led: Trial I - Curve of soil incubation with calcium carbonate; Trial II - Curve of dosage calibration of residues and water-hyacinth compost. Trial III - Evaluation of the substitution of the CaCC>3 for residues or compost of water- hyacinth. Trial IV - Evaluation of hybrid tomato plant C-38-D Novo in function of CaC03 doses combination, residues or water-hyacinth compost. The water-hyacinth compost increase N content 2,67 %; P 51,5 %; Ca 2,30 % and Zn 5,20 % in relation to not composted water-hyacinth wastes; already the K and the Mg had diminished 66,3 %, Fe 28 %; Na 10 % and Mn 54,02 %, the water-hyacinth compost showed adequate considered contents of N for tomato plant, these results indicate that wastes and compost of water- hyacinth are efficient material for nitrogen supply. Trial I: after 45 days of incubation the application of increasing doses, 0; 2; 4; 8;12;16 and 20 tha-1 of CaCC>3 produced linear increment of soil pH passing of pH 3,6 in the treatment control for 5,44 in 20 tha'1 CaCOsdose. Trial II: application of 20 tha"1 of water-hyacinth waste produced pH increase similar that one produced by 3 tha4 of calcium carbonate dose, increasing soil pH until a value of 4,03. The application of 20; 30 and 40 tha"1 dose of water-hyacinth waste and all doses of water-hyacinth compost had resulted in content reduction of soil dry matter. Trial III: the application of 3 tha'1 of CaCC>3 + 30 tha"1 of water-hyacinth compost presented greater dry matter increase. All treatments had promoted reduction of potential soil acidity (H+Al) being different of the control treatment. All the treatments that had received 9 and 12 t ha'1 of CaCC>3 had shown statistical different of control treatment (CV=11,83%). Trial IV: there was not significant statistical difference conceming the variable height of the plant, among CaCC>3 and water-hyacinth waste and water-hyacinth compost dosages. The aluminum saturation (m%) had negative influence in the plant’s diameter therefore the treatments (TI4 and T5) with greater diameter shown aluminum saturation (m%) considered low 6,28% (T14) and average 23,94% (T5). The biggest weight of dry matter of the aerial part of plant (it does not include fruit) and weight fiuits was observed in T12 treatment that showed to improve conditions for the development of the plant in relation to the other treatments (pH 5,06; m% 0,94 %, H+Al 45 mmolcdm'3). There were no significant statistics differences found in macronutrients content (N, P, K and Mg) in the evaluated treatments. The N was the only nutrient determined with content adjusted for the tomato plant (30 gkg'1) in all the treatments. Significant difference was found in the soil pH. Incorporation to the soil of water-hyacinth compost and water-hyacinth waste allow to decrease CaCC>3 dose 38% to correct soil pH from 3,6 to 5,06. All the treatments had produced significant reduction of the potential soil acidity (H+Al) except treatment TI (20t ha'1 water- hyacinth compost + 20t ha"1 water-hyacinth waste). Incorporation to the soil of CaCC>3, water-hyacinth compost or water-hyacinth waste mixed or not, modified the CECe significantly, but in the CEC pH 7 increased was not observed. All the treatments had increased bases saturation (V%). The treatments had produced significant reduction for aluminum saturation (m%). The biggest increase of the parameters, Organic Matter (O.M.) and Carbon (C) had observed in the T2 treatment (47,33 g dm'3 M.O and 2,74 % C) that it is a foreseeable result for the fact of that the T2 corresponds to a high dose of O.M. (40 t ha'1 RA + 20 t ha'1 CA). The K was only macronutrient determined in soil with adjusted content for the tomato plant. All the treatments had produced reduction of Al+3 content but they do not differs from the treatment control. The incorporation to the soil of water-hyacinth biomass is a viable altemative to decrease the CaC03 dose to correct the soil pH (H+Al) e (V%) until adequate values to the majority of the cultures. Incorporation of composted biomass of water-hyacinth results in greater benefits for the soil than incorporation of the water-hyacinth waste without composting